A phototherapeutic fluorescent β-cyclodextrin branched polymer delivering nitric oxide. (29th April 2019) - Malanga, Milo; Seggio, Mimimorena; Kirejev, Vladimir; Fraix, Aurore; Di Bari, Ivana; Fenyvesi, Eva; Ericson, Marica B.; Sortino, Salvatore
Abstract : A water soluble b-CD-branched polymer covalently binds a fluorescein moiety for imaging and a NO photodonor for therapy that can be operated in parallel upon visible light excitation. Abstract : We report herein on a novel water-soluble β-cyclodextrin-branched polymer covalently integrating a fluorescein moiety and a nitric oxide (NO) photodonor within its macromolecular skeleton. Photoexcitation with visible light induces the parallel activation of the two chromophores, which results in the green fluorescence emission suitable for imaging accompanied by NO release for therapy. In fact, this polymer internalizes in squamous carcinoma cancer cells in vitro, visualized by fluorescence microscopy, and induces cell mortality as result of the NO photo-decaging. The non-covalent drug delivery capability of this new material is also demonstrated using a hydrophobic photosensitizer for photodynamic therapy as a probe.